Organizing pneumonia in patients with severe respiratory failure due to novel A (H1N1) influenza. (22nd July 2010) - Cornejo, Rodrigo; Llanos, Osvaldo; Fernández, Cristina; Carlos Díaz, Juan; Cardemil, Gonzalo; Salguero, Jorge; Luengo, Cecilia; Tobar, Eduardo; Romero, Carlos; Gálvez, Luis Ricardo
Abstract : The authors describe two cases that developed organizing pneumonia (OP) associated with novel influenza A(H1N1) virus. These patients were admitted to intensive care unit (ICU) because of severe respiratory failure. After initial clinical improvement, both patients worsened their condition during their second week of ICU stay, presenting fever, increasing in inflammatory parameters and worsening in oxygen exchange and respiratory mechanics. Chest x-rays and computed tomographies showed an increment on lung infiltrates, given by areas of consolidation and ground glass opacification. Although broad-spectrum antibiotics were administered, patients showed no improvement. All cultures, including bronchoalveolar lavage samples, were negative. In both cases, an open lung biopsy was performed, and histopathological examination of the specimen was compatible with OP. Both patients were successfully treated with high-dose corticoids. The aim of this report is to alert about the possibility of OP associated with novel influenza virus in patients with severe respiratory failure.